Work Esteem And Re-Branding Of Technical Education And Vocational Training From The Perspective Of Parents, Teachers And Apprentice - Alavi, Khadijah; Md. Sail, Rahim; Awang, Abd Hair (Journal of Technical Education and Training, 2012)
Several issues were raised from the study of technical and vocational education: low pay, no career path for their future, unable to get admission to university, and finally technical education and vocational training are perceived to be for school dropouts and special needs students (the disabled) (Ahmad Esa , 2010; Ramlee, 1999; Wancott, 2000; Gray, 1997; Stone, 1993; Kang and Bishop, 1986). Although various efforts have been undertaken by several agencies to encourage technical education and vocational training to the public, students and parents still prefer academic education to vocational education. Why does this phenomenon still exist despite the publicity given by many agencies? Do parents, students, teachers and school counselors, and various related parties understand the system of vocational education? Aren’t there sufficient promotion arranged? Aren’t there enough "success stories" of those doing technical education and vocational training brought to light by local media? This qualitative study was conducted in two zones, namely, the north (Kedah) and central zone (Selangor), two schools were chosen from each zone; one school in the city (Kajang) and one from the rural (Dengkil), which are sufficient to get the views of  parents and teachers. The results showed that there was a positive response from parents and teachers about the work reputation and re-branding of technical education and vocational training. Technical and vocational fields are no longer targeted for weak students; on the other hand this study has shown that parents believe that girls too can become successful mechanics. Now parents and teachers are encouraging students to pursue their field of interest, and no longer judge them based on test results per se to take up tertiary education. The path of technical education and vocational training can be advanced to university level and continued abroad. There are suggestions that opportunity should also be given to students learning Arabic or Islamic studies to pursue technical education and vocational training. Openness to technical education and vocational training can improve the image, work esteem and the re-branding of its career path to achieve the status of industrialized nation in 2020. Some implications of the study have been submitted for policy makers to take proactive steps in generating and enhancing the promotion of technical and vocational training.